Evolution and effects of mobile cloud computing, middleware services on cloud, future prospects: A peek into the mobile cloud operating systems - Kotwal, Priya. A.; Singh, Adwitiy. R. (2012 IEEE International Conference on Computational Intelligence and Computing Research, 2012)
In this paper, we discuss the advent of mobile cloud computing and its advancements. It presents a review on the concept of Mobile Cloud Computing, features, statistics and growth of cloud computing, consumption of mobile services, issues in mobile cloud computing as well as prospective solutions, future scope and research. In the future scope, we discuss that the advanced mobile cloud computing platform has not only led to an improvement in the processing of mobile applications and services but has also opened a revolutionized realm wherein mobile cloud computing can be applied to the operating systems installed in mobile devices and the operating systems as a whole can run on the cloud framework, increasing the processing speed and optimizing operations to attain efficient results.